The Blockchain Technology as a New Approach of Promoting Organic Products to the Market - Chychkalo-Kondratska, Iryna; Tytarenko, Lyubov; Kalnik, Olexandr; Novytska, Iryna (International Journal of Engineering and Technology, 2018)
The authors analyze the problem of promotion of organic products both to the domestic and foreign markets. The approaches to the definition of the essence of concepts "organic products" and "blockchain technology" are generalized. The brief analysis of organic products market is provided; the prospects of market development are set. The basic tools of promotion of organic products both to the domestic and international markets are determined. It is proposed to use a new blockchain technology in the logistics chain as a part of promotion of organic products to the market. The positive and negative aspects of the interaction of the blockchain technology with logistics are revealed. This technology, due to its positive characteristics, will increase the number of potential consumers of organic products, in particular through more sophisticated and transparent supply of organic products not only to the domestic, but also to the international markets.Â Â